Pengembangan Media Pembelajaran Lectora Inspire Berbasis Pendekatan Contextual Teaching and Learning (CTL) pada Materi Asam Basa - Mardhatillah Mardhatillah; Herlinawati Herlinawati (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Mastery of learning media by educators is an important element in the learning process, because learning media can increase interest, curiosity, and motivation to learn. This study aims to determine the feasibility and response of students to Lectora Inspire learning media based on the Contextual Teaching and Learning (CTL) approach on acid-base materials. A type of R&D (Research and Development) research with a 4D (Define, Design, Develop, and Disseminate) development model. The instruments used were in the form of material and media feasibility assessment sheets, student response questionnaires using the Likert scale. The research subjects consisted of 3 lecturers of Chemistry Education at the State University of Medan, 2 chemistry teachers of SMA S Pertiwi Medan, and 15 students of SMA S Pertiwi Medan, and the object of the research was Lectora Inspire learning media based on the Contextual Teaching and Learning (CTL) approach on acid-base materials. Data collection techniques used interviews, literature studies, and questionnaires. The results of the material feasibility test were obtained with a percentage of 88.5% and media feasibility was obtained with a percentage of 91.3% which had the criteria of